Assessment of immune responses to Brucella abortus S19 vaccination in cattle and buffaloes - Shome, Rajeswari; Yallanur Konda, Prabhakar; Skariah, Somy; Shanmugam, Gandu; Muninarayanaswamy, Praveen Kumar Attiganahalli; Nagaraja, Pavan Kalyan; Megha, Kirti; Thimmappa Rajeshwari, Nanditha; Mohandoss, Nagalingam (Frontiers in Immunology, 2025)
IntroductionThe Brucella abortus S19 vaccine remains the global reference standard for bovine brucellosis prevention. This study comprehensively evaluated the safety and immunogenicity of S19 at a dose of 4 × 109 colony-forming units (CFU) in cattle and buffalo calves.MethodsA total of 180 female calves (90 cattle and 90 buffalo calves) aged 4–8 months were equally distributed across six postvaccination intervals (15 animals/group/species for days postvaccination [DPV] intervals: DPV < 21, 21–45, 46–60, 61–90, 91–120, and > 120 days). All calves were confirmed seronegative for anti-Brucella antibodies by Rose Bengal Plate Test (RBPT) and indirect enzyme-linked immunosorbent assay (ELISA) prior to vaccination. Vaccinated animals were monitored for 3 weeks for adverse effects. Humoral immunity was assessed using RBPT and Serum Agglutination Test (SAT); antibody isotypes immunoglobulin M (IgM)/immunoglobulin G (IgG) were quantified by indirect ELISA, cytokines tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-8, and IL-10 were measured by competitive inhibition ELISA, while IL-12, IL-1β, and interferon gamma (IFN-γ) were quantified using high-sensitivity sandwich ELISAs. All samples were processed by cold centrifugation (4°C) and stored at − 20°C until analysis.ResultsNo local/systemic reactions were observed, confirming safety. Significant humoral responses (p < 0.05) peaked at DPV interval < 21 (SAT: 640 IU/mL), declining gradually but persisting beyond 120 DPV. Cattle calves showed faster IgM-to-IgG switching (p < 0.05), with peak IgM (179.2 ± 5.5 vs. 163.7 ± 5.9) and IgG (220.6 ± 13.9 vs. 187.5 ± 9.5) in cattle versus buffalo calves. Proinflammatory cytokines (TNF-α, IL-6, IL-8, IL-12, IL-1β) and IL-10 peaked at DPV interval 46–60 (p < 0.05). IFN-γ (Th1 marker) peaked earlier, at DPV interval 21–45 (cattle 307.7 pg/mL ± 13.4 pg/mL vs. buffalo 274.2 pg/mL ± 11.7 pg/mL, p < 0.05), indicating robust CMI. All comparisons were performed using one-way ANOVA (GraphPad Prism 10), with significance set at p < 0.05.ConclusionB. abortus S19 at 4 × 109 CFU/dose safely induces durable humoral and cellular immunity in both species, with cattle mounting faster adaptive responses than buffaloes. The comprehensive immune profile supports its use as an effective vaccination strategy.